Implications of Oral Presentation for Fostering Learners’ Autonomy: A Case Study with Saudi Learners Majoring in English as a Foreign Language - Suliman, Wijdan (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2022)
The present paper focuses on pinpointing the implications of Oral presentation for fostering learners’ autonomy by employing experimental and qualitative research methods. The study investigated a group of participants comprised of 15 students majoring in English as a foreign language (EFL) at Qassim University. The key data was collected from the participants who were interviewed through a focusing group interview conducted on purpose to obtain a deeper insight into Saudi learners’ perceptions of how oral presentation provides opportunities for them to foster autonomy learning. The results are enlightening, as the students of College of Science and Arts in Al Asyah comprised in the sample find an overall positive satisfaction with the oral presentation as they believed that oral presentation did not only help them decide on materials, plan and prepare it for a class presentation but also it provided them with motivation to learn English, gained self-esteem, confidence and become active learners. Finally, oral presentation stimulated learners to create their own identity of learning the English language and enabled them to sort out their learning materials that satisfy their learning needs.